Penerapan Teknik Sinematografi Director Of Photography pada Produksi “Kopi Manglayang: Nafas Petani dari Lereng Gunung” - Ryan Krisna Gautama; Saeful Fatah Zaelani; Encang Saepudin; Rifky Adinur Zein (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
This study discusses the application of cinematography in the production of the feature video entitled “Kopi Manglayang: Nafas Petani dari Lereng Gunung.” The work was created to portray the lives of coffee farmers on the slopes of Mount Manglayang through a humanistic visual approach. The objective of this study is to analyze the implementation of cinematographic elements, including composition, shot types, camera movement, lighting, and color tone in supporting visual storytelling. The research method used is a qualitative descriptive method with a creation-based approach involving pre-production, production, and post-production stages. Data were obtained through field observations, interviews with coffee farmers, literature studies, and documentation during the production process. The results show that the use of cinematographic techniques plays an important role in strengthening emotional messages and presenting the realities of farmers’ lives more deeply. Long shots and extreme long shots were utilized to emphasize the natural landscape of Mount Manglayang, while medium shots and close-ups were used to capture expressions and work activities of the farmers. Natural lighting and warm color tones also contributed to building an intimate and realistic atmosphere. Therefore, cinematography in this feature video not only functions as a visual aesthetic element, but also as a storytelling medium capable of increasing audience empathy toward local coffee farmers.